Effect of Accelerated Aging on Color Stability of Two Silica-Based Ceramics with Leucite and Lithium-Disilicate Crystalline Phases After Glazing and Polishing - Mansoreh Mirzaie; Aiob Pahlavan; Tabassom Hooshmand; Hoda Safaee; Reihaneh Khalesi Tooyrekani (Islamic Dental Association of Iran, 2018)
Background and Aim: Color match between prosthetic restorations and natural teeth is challenging in dentistry. The aim of the current study was to assess the effect of accelerated aging on color stability of two silica-based ceramics with leucite and lithium disilicate crystalline phases after glazing and polishing surface treatments. Materials and Methods: In this experimental study, 30 disc-shaped specimens (1.5x10mm) of IPS e.max Press and Ceramco III ceramics were fabricated according to the manufacturers' instructions. The specimens were randomly divided into two groups of surface treatments (glazing and polishing) and were then subjected to accelerated aging for 300 hours. Color parameters were measured before and after aging using a spectrophotometer. The L*, a* and b* parameters and the color change (∆E) of ceram-ics (based on the CIE L*a*b* system) before and after glazing were determined by spectrophotometry. Data were analyzed using two-way ANOVA and t-test. P<0.05 was considered statistically significant. Results: After 300 hours of aging, the color stability (∆E), ∆L and ∆b of polished group was less than that of glazed group. The two ceramic types were not significantly different in terms of ∆E (range: 1.31 to 2.53; P=0.055). Conclusion: Glazed silica-based ceramics had higher color stability than polished ceramics after aging in our study. Color stability of silica-based ceramic systems was influenced by the surface texture and not the type of crystalline phase.